2011
DOI: 10.1007/s13178-011-0073-y
|View full text |Cite|
|
Sign up to set email alerts
|

The “Persuadable Middle” on Same-Sex Marriage: Formative Research to Build Support among Heterosexual College Students

Abstract: Same-sex marriage is a controversial policy issue that affects the welfare of gay and lesbian couples throughout the USA. Considerable research examines opinions about same-sex marriage; however, studies have not investigated the covariates of the "persuadable middle"-those individuals who are neutral or unsure about their views. This group of people is often the target of same-sex marriage campaigns, yet they have received no empirical attention.Using a sample of heterosexual college students, we conduct mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Researchers have also found high levels of support for laws protecting LGBTQ people from housing and job discrimination (Lax and Phillips 2009;Lewis and Rogers 1999;Powell et al 2010). Consistently, research shows that women, higher educated people, nonreligious individuals, younger generations, and political liberals are more likely to support these pro-LGBTQ policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2005;Lewis 2011;Lewis and Gossett 2008;Olson, Cadge, and Harrison 2006;Pearl and Galupo 2007;Rowatt et al 2009;Sherkat, de Vries, and Creek 2010;Swank, Woodford, and Lim 2013;Whitehead 2010;Woodford et al 2012).…”
Section: Lgbtq Rights In a Postmarriage Contextmentioning
confidence: 92%
“…Researchers have also found high levels of support for laws protecting LGBTQ people from housing and job discrimination (Lax and Phillips 2009;Lewis and Rogers 1999;Powell et al 2010). Consistently, research shows that women, higher educated people, nonreligious individuals, younger generations, and political liberals are more likely to support these pro-LGBTQ policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2005;Lewis 2011;Lewis and Gossett 2008;Olson, Cadge, and Harrison 2006;Pearl and Galupo 2007;Rowatt et al 2009;Sherkat, de Vries, and Creek 2010;Swank, Woodford, and Lim 2013;Whitehead 2010;Woodford et al 2012).…”
Section: Lgbtq Rights In a Postmarriage Contextmentioning
confidence: 92%
“…Consistently, scholarship indicates that women, higher educated people, non-religious individuals, younger generations, and political liberals are more likely to support pro-LGB policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Pew Research 2013a, 2013b, 2014aRowatt et al 2009;Sherkat et al 2010;Whitehead 2010;Swank et al 2013;Woodford et al 2012). Particularly relevant to the current analyses, scholars have also pointed to regional differences to explain variation in support of pro-LGB policies.…”
Section: Literature Review Public Opinion Of Pro-lgb Policiesmentioning
confidence: 58%
“…Yet such support and acceptance is higher among certain segments of the population than others (Hopkins et al 2013;Moore and Stambolis-Ruhstorfer 2013;Seidman 2002). Studies show that younger people, women, non-religious, and those who know an LGB person support pro-LGB policies at higher levels than other groups (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Rowatt et al 2009;Sherkat et al 2010;Swank et al 2013;Whitehead 2010;Woodford et al 2012).…”
mentioning
confidence: 99%
“…Public opinion studies, however, show that levels of support vary among demographic, political, and religious groups (Baunach, 9 2012;Lewis, 2003;Olson, Cadge, and Harrison, 2006;Pew Research, 2013a;Powell, Yurk Quadlin, and Pizmony-Levy, 2015). Consistently, studies find that women, higher educated people, non-religious individuals, younger generations, and political liberals support same-sex marriage at higher levels than men, lower educated people, religious individuals, older generations, and political conservatives (Andersen and Fetner, 2008;Brumbaugh et al, 2008;Galupo and Pearl, 2007;Haider-Markel andJoslyn, 2005, 2008;Kreitzer, Hamilton, and Tolbert, 2014;Lewis, 2011;Lewis and Gossett, 2008;McCarthy, 2015McCarthy, , 2014Sherkat, de Vries, and Creek, 2010;Whitehead, 2010;Woodford et al, 2012). Also, work has shown that heterosexual people who report having a personal connection to gay, lesbian, and bisexual individuals are more likely to have a positive attitude towards gay rights (Fetner, 2016;Herek, 2002;Herek & Capitanio, 1996).…”
mentioning
confidence: 88%